Static electronic baropodometry in patients with metatarsalgia - Costa, Renan Marson; da Silva, Joao Luiz Vieira; Marconato, Gianfrancesco; Morais, Sarah Carolina Diogo de; Rocha, Maria Thereza Burko (Scientific Journal of the Foot & Ankle, 2019)
Objective: To analyze the values obtained by electronic baropodometry in patients with metatarsalgia. Methods: A retrospective observational study of medical data (gender, height, weight, body mass index, foot laterality, shoe size and clinical diagnosis) and values obtained by static electronic baropodometry (load distribution and maximum and mean pressure) was performed. A total of 39 patients with clinical complaints of metatarsalgia were selected and subjected to static electronic baropodometry. Results: Female gender was more prevalent (58.9%) among patients, and 61.53% of the patients were overweight or obese. The mean maximum pressure was 1.76kgf/cm2, and the forefoot-to rearfoot load distribution ratio was 0.86. There was a significant correlation between body mass index and maximum pressure. No correlation was found with shoe size. Conclusion: The baropodometry values measured in this study were similar to those reported in the literature. Obese and overweight patients had a higher maximum pressure value, which suggests a higher risk of metatarsal pain in this population. Level of Evidence III; Diagnostic Studies; Study of non consecutive patients; Without consistently applied reference “gold” standard.